Russia's foreign and security policy in Syria: historical relations, Cold War paradigms, and contemporary geopolitics - Raquel Jorge Trujillo (Frontiers in Political Science)
IntroductionThis paper examines Russia's diplomatic and security strategy in Syria, placing its engagement in the larger framework of Cold War history and Russian-Syrian ties. The study clarifies how Russia's strategic objectives in the region, especially in connection to its “near abroad” policy, have been molded by the complex historical relationships between Moscow and Damascus.MethodsThe methodology consists in a qualitative approach, applying the security matrix model to the Russian foreign policy in Syria. From a comparative approach, the study draws attention to the similarities between Russia's military activities in Syria and Ukraine, illuminating the intricate relationship between intervention and sovereignty in both situations. The article also critically evaluates how the Kremlin has framed its engagement in Syria as a counterterrorism measure, arguing that this narrative helps to justify its actions both at home and abroad.Results and discussionBy highlighting the connections between historical background, security strategy, and current geopolitical dynamics, the study's findings show that the intervention in Syria is anchored in a deeply rooted policy in Russia, elaborated on a Cold War heritage towards the U.S. and on new concepts of multi-polarity. The study ultimately aims to offer a deeper explanation of Russia's motives in Syria. The paper adds to the discussion of Russian foreign policy and its effects on international relations and regional stability by using this perspective.